Management of the employment of people with disabilities as practised in hospitals in Warsaw - Machaj, Małgorzata; Lorkowski, Jacek; Kotela, Ireneusz (European Journal of Clinical and Experimental Medicine, 2014)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This paper presents the economic aspects of implementing a conscious policy to employ people with disabilities and special needs. The authors compare employment at three Warsaw hospitals in December 2013. Those hospitals and their respective founding bodies were the Central Clinical Hospital of the Ministry of the Interior in Warsaw (the Ministry of the Interior), the Institute of the Mother and Child (the Ministry of Health) and the Praga Hospital of the Church of the Transfiguration of Our Lord, which was transformed from an Independent Public Health Care Organisation into a Limited Liability Company on 1 July 2013, and the founding body is the City of Warsaw. Employment is analysed in terms of occupational groups, jobs occupied and the degree and code of disability. So too, the economic performance of hospitals with a conscious policy to employ people with disabilities. Employing people with disabilities not only offers benefits to the operation of an organization, but builds a positive image of the employer in the eyes of employees and contractors. People with disabilities often are highly skilled employees. They are ambitious, conscientious and hardworking. Few employers appreciate the importance of employing of people with disabilities, or the incentives and benefits they are entitled to for doing so.